FAKTOR-FAKTOR YANG MEMPENGARUHI OPTIMALISASI APBD BERBASIS KINERJA (STUDI EMPIRIS PADA KABUPATEN INDRAGIRI HILIR PROVINSI RIAU) - Rasyid, Abdul; Sari, Ria Nelly; Rasuli, M. (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2017)
Performance-based budgeting aims to streamline, streamline and economize localrevenue and expenditure budgets in budgeting. Most government organizations have not been able to implement and implement a performance-based budget and the optimal use of regional financial information systems, both provincial and district governments become the problem every year is no exception to the Government of Indragiri Hilir Regency of Riau Province.The above issues need to be investigated on the causes with the title of research factors affecting performance-based APBD optimization. The purpose of this study to determine the influence of factors that affect the optimization of APBD- based performance. By using the method of mixed research and convergent approach of this research conduct questionnaires and interviews of respondents, the type of data used is primary and secondary data that is data obtained directly from respondents and data related to the subject of research.Based on the results of leadership quality data test, organizational commitment, administrative improvement, resources, reward and punishment, strong desire to succeed, regional financial information system affect the optimization of revenue and expenditure budget based on performance, with significant level is 95% and error rate 5%. In the hypothesis test results that leadership variables, organizational commitment, administrative improvements, resources, rewards and punishment, strong desire to succeed, regional financial information systems affect the optimization of revenue and expenditure budget based on performance, with a significant level 95% t table (1.960) Smaller than t arithmetic.